ANNUAL CARBON CAPTURE POTENTIAL IN BANANA GARDENS OF INDIA - Arkalgud Ganeshamurthy (BIOTROPIA, 2023)
The global interest in increasing the world's carbon stocks is skewed towards perennial woody ecosystems. But a continuous shortage of land stands in the way of achieving the goal. We must therefore aim to explore viable alternatives. The banana as a potential carbon sequester attracted little attention from researchers. Therefore, this study aimed at estimating the potential of bananas in different states of India as potential carbon sequesters. Data was collected from twelve major banana producers between January 2021 and December 2022. One hundred banana gardens were sampled in each of the 12 banana-producing states, covering the major bananas grown (AAA, AAB, and ABB). The above-ground (AGB) and below-ground (BGB) biomass were calculated using the allometric equation with pseudostem volume as the allometric parameter. The dry weight obtained from the allometric equations was then converted to carbon using a dry weight to carbon conversion factor. Sequestered carbon varied with the AAA, AAB, and ABB of bananas. Banana plant carbon stock was also found to be very small, ranging from 2.573 to 6.407 t/ha, compared with very high soil carbon ranging from 39.55 to 77.14t. In all the banana-cultivating states, the proportion of carbon contained in the plant to that in the soil was only 8.286 percent, and that of soil carbon accounted for 91.714%. At the national level, the banana crop sequestered 48.627 million metric tonnes of carbon, with soil carbon accounting for 44.798 metric tonnes and plant carbon accounting for only 3.828 metric tonnes per year. Despite these small amounts of plant carbon, the banana cropping system enriches the soil by enabling much more carbon to be sequestered into the soil in amounts comparable to other perennial plantations.